Advanced Techniques in Bone Regeneration 2016
DOI: 10.5772/63266
|View full text |Cite
|
Sign up to set email alerts
|

Doped Bioactive Glass Materials in Bone Regeneration

Abstract: In the arena of orthopaedic surgery, autograft is considered to be the gold standard for correction of fracture repair or other bone pathologies. "ut, it has some limitations such as donor site morbidity and shortage of supply, which evolved the use of allograft that also has some disadvantages such as immunogenic response to the host, low osteogenicity as well as possibilities of disease transmission. Despite the benefits of autografts and allografts, the limitations of each have necessitated the pursuit of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 307 publications
(321 reference statements)
0
46
0
9
Order By: Relevance
“…There is some evidence that the antibacterial effect of bioactive glass can be further improved by doping them with metal ions such as zinc, strontium or silver [87]. These materials in themselves have antimicrobial properties [88]. In a recent study be Mestres et al (2010), for example, magnesium-containing cements were shown to have intrinsic antimicrobial activity and were sufficient alone, to significantly improve the health state of animals [37].…”
Section: Other Antimicrobial Materialsmentioning
confidence: 99%
“…There is some evidence that the antibacterial effect of bioactive glass can be further improved by doping them with metal ions such as zinc, strontium or silver [87]. These materials in themselves have antimicrobial properties [88]. In a recent study be Mestres et al (2010), for example, magnesium-containing cements were shown to have intrinsic antimicrobial activity and were sufficient alone, to significantly improve the health state of animals [37].…”
Section: Other Antimicrobial Materialsmentioning
confidence: 99%
“…It was shown that BGs considerably improved mineralization and cell activities when used as parts of biocomposites for periodontal tissue regeneration (Ana Isabel Leal, ; Mota et al, ). Different ions were incorporated into BG compositions, and their effects have been investigated (Nandi, Mahato, Kundu, & Mukherjee, ). Boron (B)‐incorporated BGs are used in regenerative medicine due to their positive effect on release of growth factors and increased turnover of the extracellular matrix (Gorustovich, Guglielmotti, Porto Lopez, & Cabrini, ).…”
Section: Introductionmentioning
confidence: 99%
“…Boron (B)‐incorporated BGs are used in regenerative medicine due to their positive effect on release of growth factors and increased turnover of the extracellular matrix (Gorustovich, Guglielmotti, Porto Lopez, & Cabrini, ). Inclusion of B into BGs enhances their biodegradation and bioactivity properties (Fernandes et al, ; Nandi et al, ; Yang et al, ). In previous studies, positive effect of B on osteogenic differentiation of MC3T3‐E1 pre‐osteoblastic cell was shown (Gümüşderelioğlu et al, ; Hakki, Bozkurt, & Hakki, ).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The first bioactive glass, 45S5 Bioglass ® was reported by Hench et al in 1969. 26 In this work, 45S5 base glasses, modified with the addition of silver up to 2% in weight, were prepared by melt-quenching and their structure, morphology, electrical, and antibacterial activity measurements were performed. 14 Bioglass ® presents higher bioactivity, having been applied in more than 1 million patients for jaw defects repair and orthopedic-related interventions.…”
Section: Introductionmentioning
confidence: 99%
“…25 Due to its highly promising antibacterial and anti-inflammatory properties, silver-doped bioactive glasses are considered very useful for tissue engineering applications. 26 In this work, 45S5 base glasses, modified with the addition of silver up to 2% in weight, were prepared by melt-quenching and their structure, morphology, electrical, and antibacterial activity measurements were performed. The major topic is to evaluate the antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%